2018
DOI: 10.1111/all.13655
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic inhibition of hypoxia‐inducible factor (HIF)‐hydroxylases ameliorates allergic contact dermatitis

Abstract: Citation for published version (APA): Manresa, M. C., Smith, L., Casals-Diaz, L., Fagundes, R. R., Brown, E., Radhakrishnan, P., ... Steinhoff, M. (2019). Pharmacologic inhibition of hypoxia inducible factor (HIF)-hydroxylases ameliorates allergic contact dermatitis. Allergy, 74(4), 753-766. https://doi. ABSTRACTBackground: When an immune cell migrates from the bloodstream to a site of chronic inflammation, it experiences a profound decrease in microenvironmental oxygen levels leading to a state of cellular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…deferoxamine, DFO) (Wang & Semenza, 1993), or molecules which compete for 2-oxoglutarate (Mole et al 2003). Modulation of PHD enzyme activity is beneficial in promoting anti-inflammatory responses by selectively inducing cell death in monocytes (Crifo et al 2019), neutrophils (Manresa et al 2019), and enhancing intestinal epithelial barrier function (Cummins et al 2008), in pro-angiogenic responses via the HIF-dependent upregulation of vascular endothelial growth factor (VEGF), offering protection in ischaemic disease (Milkiewicz et al 2004), as well as helping ameliorate anaemia in patients with kidney disease by stimulating erythropoietin (EPO) production and regulating iron absorption and metabolism (Chen et al 2019b,c).…”
Section: Pharmacological Hydroxylase Inhibition and Glycolysismentioning
confidence: 99%
See 1 more Smart Citation
“…deferoxamine, DFO) (Wang & Semenza, 1993), or molecules which compete for 2-oxoglutarate (Mole et al 2003). Modulation of PHD enzyme activity is beneficial in promoting anti-inflammatory responses by selectively inducing cell death in monocytes (Crifo et al 2019), neutrophils (Manresa et al 2019), and enhancing intestinal epithelial barrier function (Cummins et al 2008), in pro-angiogenic responses via the HIF-dependent upregulation of vascular endothelial growth factor (VEGF), offering protection in ischaemic disease (Milkiewicz et al 2004), as well as helping ameliorate anaemia in patients with kidney disease by stimulating erythropoietin (EPO) production and regulating iron absorption and metabolism (Chen et al 2019b,c).…”
Section: Pharmacological Hydroxylase Inhibition and Glycolysismentioning
confidence: 99%
“…2019), neutrophils (Manresa et al . 2019), and enhancing intestinal epithelial barrier function (Cummins et al . 2008), in pro‐angiogenic responses via the HIF‐dependent upregulation of vascular endothelial growth factor (VEGF), offering protection in ischaemic disease (Milkiewicz et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it is reported that PHD inhibition reduced TNF-α-induced production of inflammatory chemokines in keratinocytes and ameliorated allergic contact dermatitis [15]. Therefore, we hypothesized that hypoxia of epidermal tissue control TSLP expression, too.…”
Section: Introductionmentioning
confidence: 95%
“…As TNF-TNFR2 interaction contributes to the exacerbation of AD, targeting TNF-TNFR2 in AD is a promising therapy [43]. HIF hydroxylases and HIF pathway have been reported in AD, and pharmacologic inhibition of HIF hydroxylases has been suggested to be a novel therapeutic approach in treating allergic contact dermatitis [44]. Although AD is a Th2-dominated disease with overexpression of IL-4, IL-5, and IL-13, the dysregulation of IL-17/Th17 in AD was reported in several studies [45,46].…”
Section: Discussionmentioning
confidence: 99%